Linux foundation certified system administrator (LFCS). (LiveLessons (Indianapolis, Ind.), 2023)
20+ Hours of Video Instruction Your full resource to successfully study for the Linux Foundation Certified System Administrator (LFCS) exam Linux Foundation Certified System Administrator (LFCS) Complete Video Course, 3rd Edition is a comprehensive video training that will teach you core Linux concepts and usage along with clear explanations on the objectives of the LFCS exam. To offer this course in a way that is most efficient for you, the contents have been developed to build on your existing Linux knowledge. You will start with Linux Fundamentals, 2nd edition, a full video course on Linux basics, concepts, practices, and theories so you can get the foundational knowledge you need. You will then dive into the core part of the LFCS exam--including Advanced System Administration--and managing storage, security, SSH services, and virtualization. Each lesson ends with a lab for you to practice the skills learned in each lesson. These labs also act as training for the hands-on LFCS exam. The LFCS section explores more advanced LFCS topics. It covers Advanced Systems Management; security; storage; containers and virtualization; and open-source solutions. The course then ends with a practice exam so you can test your skills, compare your answers to mine, and get a feel for the exam before you take the test. Topics included in course: Linux Fundamentals, 2nd Edition Module 1: Essential Commands Module 2: User and Group Management and Permissions Module 3: Operating Running Systems Linux Foundation Certified System Administrator (LFCS) Module 1: Advanced Systems Management Module 2: Managing Security Module 3: Managing Storage Module 4: Containers and Virtualization Module 5: Using Essential Open Source Solutions Module 6: Practice Exam About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open-Source topics. He is the author of the best-selling Red Hat RHCSA and RHCE Cert Guides as well as a number of other titles on Kubernetes (including CKAD and CKA), Ansible, Containers, Bash, Microservices, and more. Sander also works as a Linux and DevOps instructor, teaching onsite and online classes for customers around the world. Skill Level : Beginner to Intermediate Learn How To : Key concepts for all the objectives on the Linux Foundation Certified System Administrator (LFCS) exam Real-life Linux administration tasks Course requirement: The ideal target student wants to learn Linux from the ground up and carry through to the LFCS exam. They will start with the Linux Fundamentals portion of the course, and then get into the details for LFCS exam prep. Who Should Take This Course : Linux Foundation Certified System Administrator (LFCS) certification candidates Anyone interested in learning about Linux from the ground up Junior system administrators who want to deepen their skills Administrators currently administering UNIX systems and developers who write software for Linux DevOps Engineers who want to build their Linux skills About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.